2(3x-3)=(4x-2)

Simple and best practice solution for 2(3x-3)=(4x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-3)=(4x-2) equation:


Simplifying
2(3x + -3) = (4x + -2)

Reorder the terms:
2(-3 + 3x) = (4x + -2)
(-3 * 2 + 3x * 2) = (4x + -2)
(-6 + 6x) = (4x + -2)

Reorder the terms:
-6 + 6x = (-2 + 4x)

Remove parenthesis around (-2 + 4x)
-6 + 6x = -2 + 4x

Solving
-6 + 6x = -2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6 + 6x + -4x = -2 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-6 + 2x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
-6 + 2x = -2 + 0
-6 + 2x = -2

Add '6' to each side of the equation.
-6 + 6 + 2x = -2 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = -2 + 6
2x = -2 + 6

Combine like terms: -2 + 6 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| (3n)(4n)= | | 2(n-3)=7k+4 | | 10x-2-5x=3x+3 | | Y=5(14)+30 | | 2x+4y=5forx | | 2x^2-10x-2100=0 | | M+15=65 | | y-9-2=5 | | 3x-8=4x-2 | | 3k^2+13k+10= | | .05x-.8=6.7 | | -h=-h+5 | | 3(4x+6)=15x+5-3x+13 | | 3x-4-2x=2x-7 | | 2x+4x^2-8x^3= | | 15+2(3x+2)=3(7+2x) | | 4-4a=36 | | x^4-x^3-9x^2+3x-18=0 | | x-8x+12=23 | | 45=-5X-54 | | 95-m=72 | | 27=15+x+9 | | Y=-7(9)+8 | | a(2a+4b)= | | 7r^2+5r-2=0 | | p+21=15 | | 86=13x-5 | | 5x-123+8x=98 | | -10x+58=6x+41 | | 2x+3(x-3)=6x+1 | | 7-7(5m+2)=-147 | | 91=5x-24 |

Equations solver categories